Nadenke oor 500 jaar se Reformatoriese teologie - W.C. Van Wyk, Ignatius (Natie) (HTS Theological Studies/Teologiese Studies, 2017)
In 2017 we celebrate for the 500th time the Reformation of the church. The authors want to ensure that there is also a contribution in Afrikaans in this important year. The central themes of Reformation theology are discussed. Reformation theology did not end with the contributions of Luther and Calvin, and one of the authors therefore, reflects with one of the greatest theologians alive, Jürgen Moltmann, on theology and life. In the recent past, scholars such as Ebeling and Van Selms, made valuable contributions that could be used in present-day discussions on church matters and political challenges. This book is proof that these older contributions are still important for in-depth reflections on complex theological questions. This book is also an exhibition of present-day theological research at the University of Pretoria. A diversity of opinions are tolerated, with the knowledge that there is a common love for our Reformation heritage. The book follows the internationally accepted research methodology in the field of historic theology. The classical texts of the reformers, such as Luther and Calvin, are researched in the original and made accessible to the Afrikaans readership. The book is witness to the fact that we have valuable contributions to Reformation theology coming from the recent past. The contributions are also analysed within their original historic setting and hermeneutically actualised for present-day church matters. This book is an important contribution to the Afrikaans reception of Reformation theology. For the first time, important enunciations of the reformers (especially Luther) are provided in Afrikaans with the original texts in footnotes. For the first time Adrianus Van Selms' catechetical handbook, that was recently discovered in an archive, is brought into the academic discussion. As South Africans, we struggle with issues such as gender, marriage, the political role of the church and interreligious relationships. It is clear, from this research, that the older European debates are helpful in bringing depth to our contextual debates. The target audience of the book is primarily the academic fraternity in historic theology, systematic theology and science of religion. It is, however, also accessible for ministers of religion and the general public, hence almost all the Latin, German and French quotations are translated into Afrikaans. The main aim was to make an Afrikaans contribution to Reformation 500. I declare that no part of any chapter is taken from another published work without the necessary recognition. This is original research and not one of the chapters has been published somewhere else.